Laryngeal manifestations in atypical recurrent aphthous stomatitis - Miziara,Ivan Dieb (2009)
Recurrent aphthoid stomatitis is characteristically observed in children and adolescents in the form of painful relapsing ulcers in the oral mucosa unaccompanied by evidences of systemic disease. The ulcers appear every one or two weeks for at least one entire year. Some patients suspected for recurrent aphthoid stomatitis develop lesions in atypical sites - mainly in the larynx - concurrently to the ones found in the oral mucosa. AIM: this study aims to describe a series of recurrent aphthoid stomatitis patients with atypical laryngeal injuries. Study design: this is a case series study. MATERIALS AND METHOD: patients diagnosed with recurrent aphthoid stomatitis with oral mucosa ulcers and laryngeal symptoms without altered lab test results and no evidence of systemic disease underwent fibroscopic examination, oral and laryngeal biopsies, followed by specimen evaluation by direct immunofluorescence. RESULTS: all six patients in this series had acute and chronic inflammatory processes according to pathology studies and negative direct immunofluorescence test results. CONCLUSION: laryngeal involvement in recurrent aphthoid stomatitis is rare. Therefore, during diagnostic examination thorough clinical history and meticulous physical examination accompanied by fibroscopic examination are necessary. When atypical lesions are found, biopsies for histological evaluation and direct immunofluorescence tests are required.